Influence of programming attitudes, computing attitudes and thinking styles on secondary champion school teachers’ computational thinking skills - Mohd Kusnan, Rusno (2021)
Computational thinking is a skill that qualifies for the fourth industrial revolution, or better known as IR 4.0 and meets its challenges. Teachers are asked to prepare themselves with various skills as a preparatory step to face the challenges of IR 4.0 and apply 21st century skills or digital skills to students as contained in PPPM 2013 - 2025. Therefore, this study focuses on teachers in identifying the level of thinking computational, its relationship to programming and computing, and thinking style from a demographic aspect of teachers. This study uses a descriptive and correlation study design with a sampling framework from Malaysia Digital Economy Corporation (MDEC) (2020), which represents ten Mydigitalmaker champion secondary schools in Malaysia that provide computational thinking training and continuous professional development. A total of 252 teachers were involved and selected by systematic random sampling using Microsoft excel. At the same time, the use of instruments based on previous research instruments and modifications to the items made so that they are relevant and appropriate to the current study. Modifications have been made after getting permission from the original developer of the instrument. The results showed that programming attitude, computing attitude, and thinking style were significant in predicting computational thinking among Mydigitalmaker champion secondary school teachers in Malaysia. The impact of the study provides the finding that teachers today who have been exposed to computational thinking skills can apply these skills to their students effectively. Therefore, it is necessary to educate students in ways of cultivating programming attitudes, computing attitudes, and thinking styles that are related to the successful development of computational thinking skills. It is hoped that this study can benefit school principals and teachers, policy makers, and the ministry of education (MoE) in setting the expected criteria for the recruitment of new teachers and the formation of 21st century students.